Consumer Satisfaction Index (CSI) of Subsidized Certified Rice Seeds Attributes at Malang Regency, East Java, Indonesia - Riyanti Isaskar; Rini Dwiastuti; Nur Baladina; Anisa Aprilia; Putri Budi S. (Institute of Research and Community Service, University of Brawijaya)
The aims of this research are to analyze subsidized certified rice seeds attributes, and measure the satisfaction level of certified subsidized rice seeds. 150 sample of farmers from 15 villages are used to answer the research questions. This research use methods of Importance Performance Analyses (IPA) to analyze the attributes of subsidized certified rice seeds and Consumer Satisfaction Index (CSI) to measure the level of satisfaction of the product (rice seed). The results indicate 8 attributes that fall into the category of attributes that are primarily prioritized for improvement, among others, seeds can be obtained easily and affordable, the availability of seeds can be ascertained, the purity of the seeds reaches more than 95%.The accuracy of seed quality, accuracy of seed quantity with land area, timeliness of seed distribution, and synchronization at nursery, and synchronized growth at 1 month. While the index of consumer satisfaction is in the range of 0.60 to 0.79 which means the average consumer has been satisfied but the consumer's satisfaction has not been maximized.